Crypto Art: NFT Art Trading and the Art Market (Asian Journal of Social Science Studies, 2022)
This article introduces what NFT art is and what virtual art trading is and analyses the advantages, disadvantages, and current status of NFT art. It also discusses how NFT artworks have changed the trend and demand in the art market.